Sistem Informasi Geografis Tanah Bersertifikat Pada Desa Kersik Kecamatan Marangkayu Kabupaten Kutai Kartanegara - Franz, Annafi; Salman, Salman; Satria, Bagus (Universitas Pelita Bangsa, 2023)
The development of information technology is currently causing significant changes in various fields including community administration services at the Village Office. One of the information technologies used is a Geographic Information System (GIS) which is used as a tool for storing, manipulating, analyzing and displaying spatial data and its attributes. Kersik Village in Marangkayu Sub-District, Kutai Kartanegara District currently does not yet have a functioning certified forest information system, thus attacking the community in accessing information about certified land. Therefore, a geographic information system for certified land is needed in Kersik Village to make it easier for the community to access information related to certified land. This system will also assist the village government in managing certified land data, such as location, area, and landowner information. This system is expected to increase efficiency and transparency in the management of certified land data in Kersik Village, Marangkayu Sub-District, Kutai Kartanegara Districk.